Enhancing Academic Performance in Mathematics of Grade 11 Students through Pre-Recorded Lesson and Home Tutorial Session - Tapado, Neilkim-Peter J. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Introduction: Under the new normal circumstances, a lot of students had the most difficulty learning effectively and succeeding in school, and they still frequently struggle. The majority of students were having problems understanding the modules and other subjects, particularly math. Consequently, students truly need the assistance of the teachers in each lesson in mathematics for the self-learning module. Method: The study employed descriptive research utilizing a quantitative approach through the comparative method to determine if there is a significant difference in the pre-test and post-test results of the students before and after giving pre-recorded lessons and home tutorial sessions. The respondents to the study were the 32 Grade 11 students at Jomalig National High School who took the General Academic Strand (GAS). Results: The findings of the study revealed that there were notable and significant differences between the pre-test and post-test scores of the students involved in the interventions. The pre-test and post-test data revealed a mean of 12.25 and 26.5312, respectively. The data also revealed a computed t-value of 24.52165006 and a p-value of 3.66137E-22 at the 0.05 level of significance, which shows that there is a significant difference in the pre-test and post-test scores of the students while giving the pre-recorded lesson and home tutorial session. The respondents were chosen purposefully. Conclusions: Giving pre-recorded lessons and home tutorial sessions had a massive effect on the academic performance in mathematics of grade 11 students; thus, these enhanced the academic performance of grade 11 students in mathematics.